The station scientist: Examining the impact of race and sex of broadcast meteorologists on credibility, trust, and information retention - Rainear, Adam M.; Lachlan, Kenneth A. (Frontiers in Communication, 2022)
Broadcast meteorologists hold a set of skills unique in a newsroom. Not only must a broadcast meteorologist utilize communication skills similar to that of a newscaster, they are also typically versed in some physical science. In addition, the field of meteorology has an unfortunate disparity when examining job statistics as they relate to race and biological sex. Generally speaking, men outnumber women in broadcast television positions three to one, and minorities are often outnumbered or excluded from coverage altogether. Drawing on Uses and Gratifications and Media System Dependency Theory, this project examined the effects of race and biological sex on the audience perceptions of forecaster trust, credibility, and information retention. Two experiments were conducted, and analysis of variance was utilized to examine the hypotheses and research questions. The first experiment tested the manipulations of forecaster race and sex in the form of a mock weather hit - using a student sample. The results generally suggest that there are mixed findings for the effects of forecaster race and sex on the dependent variables of trust, credibility, and information retention. The second experiment tested the same two manipulations from experiment one on a non-student sample. The results are discussed in terms of how individuals may perceive forecasters given their race, sex, or degree level, and the potential implications for processing information or forming attitudes and decisions based off this behavior.